Effects of public roads on wildlife-vehicle collisions in two protected areas, Hluhluwe-iMfolozi Park and iSimangaliso Wetland Park, in KwaZulu-Natal, South Africa - Cameron T. Cormac; Cormac Price; Wendy Collinson; Dave J. Druce; Jarryd P. Streicher; Colleen T. Downs (Global Ecology and Conservation)
Anthropogenic change is a global threat to wildlife and the biosphere's health. Wildlife faces growing threats from anthropogenic activities, especially infrastructure. Protected areas (PAs) are not exempt, particularly those that experience high traffic volumes on public road passages both within and on their peripheries. Globally, studies have found that public roads in PAs cause large numbers of wildlife-vehicle collisions (WVCs), threatening the stability of these wildlife refugia. As vehicle traffic density is increasing globally, particularly in Africa, where little research on the ecological impact of linear infrastructure has been done, the impact of roads on wildlife in protected areas must be determined. We determined the effect of public roads on vertebrate mortalities in the protected areas of Hluhluwe-iMfolozi Park (HiP) and iSimangaliso Wetland Park (ISWP), KwaZulu-Natal Province, South Africa, collected monthly in 2022 and 2023. Species composition of vertebrate mortalities, and heat maps of mortalities, combined with a suite of ecological factors, were used to identify drivers of wildlife-vehicle collisions. A total of 1606 road mortalities were recorded, with small-bodied vertebrates (< 5 kg) comprising most of the identified species. Amphibians experienced the highest number of mortalities, 1066 individuals, while birds had the highest species diversity in the mortality record with 31 identified species. High mortality levels were concentrated in areas with unsloped road surfaces and increased vehicle traffic within HiP, while the surrounding habitat had a larger influence on mortalities within ISWP. Our results showed that intervention is needed along portions of the two public roads in both protected areas, particularly during the wet season, with mortality rates as high as 13 carcasses per km. Mitigation measures should be implemented to reduce the number of wildlife mortalities along the roads in both locations, with specific measures to mitigate small vertebrate road mortalities. All planned mitigation measures should focus on the sections identified as high mortalities zones.